2011
DOI: 10.1016/j.ijantimicag.2010.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of demethylfruticuline A and fruticuline A from Salvia corrugata Vahl. on biofilm production in vitro by multiresistant strains of Staphylococcus aureus, Staphylococcus epidermidis and Enterococcus faecalis

Abstract: In this study, demethylfruticuline A (dfA) and fruticuline A (fA), two quinones representing the mayor diterpenoid components of the exudate produced by the aerial parts of Salvia corrugata, were assessed for their ability to modify surface characteristics, such as hydrophobicity, and to inhibit synthesis of biofilm in vitro by multiresistant Staphylococcus aureus, Staphylococcus epidermidis and Enterococcus faecalis. Five strains of S. aureus (three meticillin-resistant and two meticillinsusceptible), five st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 39 publications
1
30
0
1
Order By: Relevance
“…This is particularly so in consideration of the fact that the two groups of compounds may possess different and possibly novel mechanisms of molecular action, as shown by their ability to overcome the various traits of resistance to usual antibiotics carried by the Gram-positive pathogens thus far analyzed. None of these new active molecules inhibited the two Gram-negative species tested, nor C. albicans, in agreement with previous findings showing that natural compounds obtained from several plants, while active on Gram-positive species are generally inactive on Gram-negative organisms and fungi (Bisio et al, 2008;Schito et al, 2011). This lack of activity is probably due to the peculiar structure of the external layers of both groups of microorganisms, the Gram-negatives presenting a highly selective and hydrophobic outer membrane and C. albicans, a thick cell wall where b-glucans and chitin are abundant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is particularly so in consideration of the fact that the two groups of compounds may possess different and possibly novel mechanisms of molecular action, as shown by their ability to overcome the various traits of resistance to usual antibiotics carried by the Gram-positive pathogens thus far analyzed. None of these new active molecules inhibited the two Gram-negative species tested, nor C. albicans, in agreement with previous findings showing that natural compounds obtained from several plants, while active on Gram-positive species are generally inactive on Gram-negative organisms and fungi (Bisio et al, 2008;Schito et al, 2011). This lack of activity is probably due to the peculiar structure of the external layers of both groups of microorganisms, the Gram-negatives presenting a highly selective and hydrophobic outer membrane and C. albicans, a thick cell wall where b-glucans and chitin are abundant.…”
Section: Discussionsupporting
confidence: 91%
“…We recently described the antibacterial and anti-biofilm activity of two diterpene quinones from the exudation product of the fresh aerial parts of Salvia corrugata Vahl. against several Gram positive strains (Bisio et al, 2008;Schito et al, 2011). Prompted by these positive results we investigated Salvia adenophora Fernald, a Mexican species belonging to the http://dx.doi.org/10.1016/j.phytochem.2014.10.033 0031-9422/Ó 2014 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Fruticulin A is a rare compound and was reported in only two other species of Salvia, S. fruticulosa [28] and S. corrugata [29]. Previous studies showed antibacterial [29, 30] and cancer chemopreventive activities of fruticulin A [31], but anti-inflammatory assays had not been performed with this compound. To test the contribution of fruticulin A to the activities observed in the extract, we tested the compound for anti-inflammatory and antihyperalgesic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols have received some attention recently regarding their antimicrobial effect upon microorganisms in biofilms, including a small number of studies involving S. epidermidis (Ferrazzano et al, 2009;Prabhakar et al, 2010;Schito et al, 2010). Sampaio et al (2009) showed that polyphenol-rich extracts of fruits from Caesalpiniea ferrea had antibiofilm activity in a multispecies biofilm model involving Streptococcus sp., Candida albicans and Lactobacillus casei.…”
Section: Discussionmentioning
confidence: 99%